Behavioral evidence for the role of cortical θ oscillations in determining auditory channel capacity for speech - Ghitza, Oded (Frontiers in Psychology, 2014)
Studies on the intelligibility of time-compressed speech have shown flawless performance for moderate compression factors, a sharp deterioration for compression factors above three, and an improved performance as a result of "repackaging" – a process of dividing the time-compressed waveform into fragments, called packets, and delivering the packets in a prescribed rate. This intricate pattern of performance reflects the reliability of the auditory system in processing speech streams with different information transfer rates; the knee-point of performance defines the auditory channel capacity. This study is concerned with the cortical computation principle that determines channel capacity. Oscillation-based models of speech perception hypothesize that the speech decoding process is guided by a cascade of oscillations with θ as "master," capable of tracking the input rhythm, with the θ cycles aligned with the intervocalic speech fragments termed θ-syllables; intelligibility remains high as long as θ is in sync with the input, and it sharply deteriorates once θ is out of sync. In the study described here the hypothesized role of θ was examined by measuring the auditory channel capacity of time-compressed speech undergone repackaging. For all compression factors tested (up to eight), packaging rate at capacity equals 9 packets/sec – aligned with the upper limit of cortical θ, θmax (about 9 Hz) – and the packet duration equals the duration of one uncompressed θ-syllable divided by the compression factor. The alignment of both the packaging rate and the packet duration with properties of cortical θ suggests that the auditory channel capacity is determined by θ. Irrespective of speech speed, the maximum information transfer rate through the auditory channel is the information in one uncompressed θ-syllable long speech fragment per one θmax cycle. Equivalently, the auditory channel capacity is 9 θ-syllables/sec.